EFFECTS OF PRACTICE STYLE ON A COMPLEX GYMNASTICS SKILL PERFORMANCE OF HIGH-, MEDIUM-, AND LOW-SKILLED LEARNERS - Michalis Proios (University of Ljubljana Press (Založba Univerze v Ljubljani), 2019)
This study examined the effect of the practice style of teaching in teaching a complex gymnastic skill and compared the achievements of low, medium and high skilled learners on motor skill performance. 46 students of the first highschool grade aged 12-14 years, of two classes, were taught using practice style of teaching the handstand forward roll during (12) lessons, 30 minutes each, 2 times per week. The skill performance has been recorded and evaluated prior, post and two weeks after the end of the program. Based on the initial compound measurement scores, students were grouped into three equal groups of low, medium and high skill. The 3 x 3 analysis of variance (skill level group x test), with repeated measurements in the last factor showed that all the groups have improved their performance both in outcome (quantitative measurement) and in technique (qualitative measurement) of the handstand forward roll and that there were significant effects for the learners' skill level. This study showed that low skilled learners improved to a greater extent, compared to those of medium and high skill, particularly as for the skill outcome.